Corrosion of titanium alloys in pressurised water at 300 °C: Kinetics and modelling. (September 2021) - Selva, Sabrina; Bignon, Quentin; Raynal, Amandine; Martin, Frantz; Auzoux, Quentin; Renou, Gilles; Tabarant, Michel; Miserque, Frédéric; Latu-Romain, Laurence; Wouters, Yves
Highlights: The nanoscale TiO2 layer was covered by anatase and ilmenite crystallites. The thin TiO2 layer evolution was modelled by a Loriers-Haycock model. Titanium and ilmenite precipitation ratii were defined and measured. A phenomenological model was proposed to link mass variation to corrosion rate. Corrosion rates of all studied materials stand between 2 and 6.6 μm/year at 300 °C. Abstract: The corrosion of titanium alloys in primary water at 300 °C led to a global weight gain due to oxidation and surface precipitation, despite some dissolution. A model was proposed, taking into account the weight contribution of each oxide type to the global mass evolution with exposure time. Based on this model, on mass variation and GD-OES results, a corrosion rate ranging between 2 and 6.6 μm.year -1 at 300 °C for all tested materials was estimated. Due to the simultaneous corrosion of the used stainless steel reactors, a protective ilmenite layer finally precipitated at the surface of the samples.